Understanding methane/carbon dioxide partitioning in clay nano- and meso-pores with constant reservoir composition molecular dynamics modeling. Issue 13 (13th March 2019) - Loganathan, Narasimhan; Bowers, Geoffrey M.; Ngouana Wakou, Brice F.; Kalinichev, Andrey G.; Kirkpatrick, R. James; Yazaydin, A. Ozgur
Abstract : CRC-MD simulations show that nanopores in shales bounded by clay minerals have a strong preference for CO2 relative to CH4 . Abstract : The interactions among fluid species such as H2 O, CO2, and CH4 confined in nano- and meso-pores in shales and other rocks is of central concern to understanding the chemical behavior and transport properties of these species in the earth's subsurface and is of special concern to geological C-sequestration and enhanced production of oil and natural gas. The behavior of CO2, and CH4 is less well understood than that of H2 O. This paper presents the results of a computational modeling study of the partitioning of CO2 and CH4 between bulk fluid and nano- and meso-pores bounded by the common clay mineral montmorillonite. The calculations were done at 323 K and a total fluid pressure of 124 bars using a novel approach (constant reservoir composition molecular dynamics, CRC-MD) that uses bias forces to maintain a constant composition in the fluid external to the pore. This purely MD approach overcomes the difficulties in making stochastic particle insertion–deletion moves in dense fluids encountered in grand canonical Monte Carlo and related hybrid approaches. The results show that both the basal siloxane surfaces and protonated broken edge surfaces of montmorillonite both prefer CO2 relative to CH4 suggesting that methods of enhanced oil and gas production using CO2 will readily displace CH4 from such pores. This preference for CO2 is due to its preferred interaction with the surfaces and extends to approximately 20 Å from them.